Chemical‐assisted femtosecond laser writing of optical resonator arrays. Issue 6 (29th September 2015) - Haque, Moez; Herman, Peter R.
Abstract : Micro‐optical resonator arrays are introduced for refractive index sensing, building on the unexplored benefits of open dielectric stacks. Femtosecond laser irradiation with selective chemical etching exploits the self‐alignment of nanograting planes to precisely align waveguide‐coupled hollow resonators and provide strong spectral resonance bands. Such high finesse optical elements open a new realm of optofluidic and optical circuit concepts with facile integration prospects towards Telecom fiber sensing networks and biomedical probes. Abstract: The design of micro‐optical resonator arrays are introduced and tailored towards refractive index sensing applications, building on the previously unexplored benefits of open dielectric stacks. The resonant coupling of identical hollow cavities present strong and narrow spectral resonance bands beyond that available with a single Fabry Perot interferometer. Femtosecond laser irradiation with selective chemical etching is applied to precisely fabricate stacked and waveguide‐coupled open resonators into fused silica, taking advantage of small 12 nm rms surface roughness made available by the self‐alignment of nanograting planes. Refractive index sensing of methanol‐water solutions confirm a very attractive sensing resolution of 6.5 × 10 −5 RIU. Such high finesse optical elements open a new realm of optofluidic sensing and integrated optical circuit concepts for detecting minute changes in sample properties against a control solution that may find importance in chemical and biological sensors, telecom sensing networks, biomedical probes, and low‐cost health care products.